PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN INDOMARET PEKANBARU - Aprima Arta; Sri Kartikowati; Rosyetti (Jurnal Economica, 2019)
Indomaret is one of the retailers in the city of Pekanbaru. In the retail industry, Indomaret face competitive competition from the other minimarket competitors. The purpose of this study is to analyze the effect of product quality, price, and service quality on customer satisfaction and loyalty of Indomaret Pekanbaru.This research was conducted at the Indomaret Pekanbaru. The data collection technique was used questionnaires. Data was then analyzed used SPSS 17.00 for Windows and SmartPLS program.The results of this study indicate that: 1) there is an affect of the product quality, price and service quality on satisfaction 2) there is an affect of product quality, price and service quality on customer loyalty 3) customer satisfaction affects the customer loyalty of Indomaret Pekanbaru 4) there is an affect of product quality, price and service quality on customer loyalty through customer satisfaction. Based on the results of the study, it is suggested to Indomaret Pekanbaru to improve customer loyalty by improving the level of product quality, price and services provided to customers.